'Plate‐like‐coral' polymer particles with dendritic structure and porous channels: Effective delivery of anti‐cancer drugs. Issue 19 (16th December 2020) - Amgoth, Chander; Dharmapuri, Gangappa; Patra, Sukanya; Wasnik, Kirti; Gupta, Premshankar; Kalle, Arunasree M.; Paik, Pradip
Abstract: ' Plate‐like‐coral' shaped polymer capsule (PC‐PLCDB) with dendritic network structure and porous channels has been synthesized and used for therapeutic purposes. First di‐block copolymer [(PEG)‐b‐(L‐AspA)n ] has been synthesized from PEG (polyethylene glycol) and aspartic acid (AspA). Then the biocompatible PC‐PLCDB has been achieved by homogeneous mixing of [(PEG)‐b‐(L‐AspA)n ] and poly‐N‐isopropyl acrylamide (PNIPAM) followed by reprecipitation. Only H‐bonding is responsible for the foundation of self‐assembly of the polymer chains and to form PC‐PLCDB. A huge extent of loading anticancer drug, for example, doxorubicin (DOX) in PC‐PLCDB is possible. in vitro study has been performed to check the therapeutic efficacy of PC‐PLCAD‐DOX formulation on chronic myeloid leukemia cells (K562). The IC50 has been calculated to be 0.405 (±0.014) ng μg −1 of the formulation. PC‐PLCAD‐DOX inhibits 80% of the cancer cell only by 1.0 μg mL −1 of the formulation. This study reveals that the PC‐PLCAD could be a promising candidate for therapeutic applications. Abstract : Self‐assembled thermo sensitive polymer capsules with coral shaped structure which was synthesized from amino acid based block‐copolymers and PNIPAM, is effective as nanomedicine and for therapeutic applications. This nanocapsule formulated with DOX is also efficient in killing the chronic myeloid leukemia cells (K562).